# Find $\dfrac{dy}{dx}$ , if $y=\log (4x-{{x}^{5}})$ .

Answer

Verified

359.4k+ views

Hint: To solve this question we should use chain rule and also remember differentiation of $\log x$ .

Complete step-by-step answer:

We will need following facts to solve this question

(a) Differentiation of ${{\log }_{e}}x$ is given by- $\dfrac{d}{dx}\left( {{\log }_{e}}x \right)=\dfrac{1}{x}$ ……….(i)

(b) Differentiation of $k{{x}^{n}}$ where k and n are constants is given by- $\dfrac{d}{dx}(k{{x}^{n}})=k.n.{{x}^{n-1}}$ ………(ii)

We have $y=\log (4x-{{x}^{5}})$ . Differentiating both sides with respect to x we get,

$\dfrac{dy}{dx}=\dfrac{d}{dx}\{\log (4x-{{x}^{5}})\}$

Now we will proceed step by step.

We differentiate first the logarithmic term with the help of equation (i) according to the chain rule

$\dfrac{dy}{dx}=\dfrac{1}{4x-{{x}^{5}}}\dfrac{d}{dx}(4x-{{x}^{5}})$

Now we need to differentiate the polynomial term. For this we write,

\[\dfrac{dy}{dx}=\dfrac{1}{4x-{{x}^{5}}}\left\{ \dfrac{d}{dx}(4x)-\dfrac{d}{dx}({{x}^{5}}) \right\}\]

Now we use equation (ii) to solve this differential. So, we have,

\[\dfrac{dy}{dx}=\dfrac{1}{4x-{{x}^{5}}}(4-5{{x}^{4}})\]

By further simplification we can write,

$\dfrac{dy}{dx}=\dfrac{4-5{{x}^{4}}}{4x-{{x}^{5}}}$

Hence, the answer is $\dfrac{4-5{{x}^{4}}}{4x-{{x}^{5}}}$

Note:

We should also keep in mind the base of the logarithm when we are differentiating. We must make the base of logarithm as e when we try to differentiate as equation (i) is only valid when the base is e.

There can be another way to solve this differentiation.

As we know,

${{\log }_{a}}b=c\Rightarrow b={{a}^{c}}$

We can use the following result too in our question and proceed.

We have, $y=\log (4x-{{x}^{5}})$

Using the above property we can write,

$4x-{{x}^{5}}={{e}^{y}}$

Again we can differentiate with respect to x both sides and proceed.

$\dfrac{d}{dx}(4x-{{x}^{5}})=\dfrac{d}{dx}({{e}^{y}})$

Now we can apply chain rule and proceed as earlier,

$(4-5{{x}^{4}})={{e}^{y}}\dfrac{dy}{dx}$

Dividing both sides with ${{e}^{y}}$ we have,

$\dfrac{dy}{dx}=\dfrac{4-5{{x}^{4}}}{{{e}^{y}}}$

Substituting y we have,

$\dfrac{dy}{dx}=\dfrac{4-5{{x}^{4}}}{{{e}^{\log (4x-{{x}^{5}})}}}$

Now we need the following property of exponential: ${{a}^{{{\log }_{a}}b}}=b$

Therefore, we can write

$\dfrac{dy}{dx}=\dfrac{4-5{{x}^{4}}}{4x-{{x}^{5}}}$

As we can see by both methods we get exactly the same answer.

Complete step-by-step answer:

We will need following facts to solve this question

(a) Differentiation of ${{\log }_{e}}x$ is given by- $\dfrac{d}{dx}\left( {{\log }_{e}}x \right)=\dfrac{1}{x}$ ……….(i)

(b) Differentiation of $k{{x}^{n}}$ where k and n are constants is given by- $\dfrac{d}{dx}(k{{x}^{n}})=k.n.{{x}^{n-1}}$ ………(ii)

We have $y=\log (4x-{{x}^{5}})$ . Differentiating both sides with respect to x we get,

$\dfrac{dy}{dx}=\dfrac{d}{dx}\{\log (4x-{{x}^{5}})\}$

Now we will proceed step by step.

We differentiate first the logarithmic term with the help of equation (i) according to the chain rule

$\dfrac{dy}{dx}=\dfrac{1}{4x-{{x}^{5}}}\dfrac{d}{dx}(4x-{{x}^{5}})$

Now we need to differentiate the polynomial term. For this we write,

\[\dfrac{dy}{dx}=\dfrac{1}{4x-{{x}^{5}}}\left\{ \dfrac{d}{dx}(4x)-\dfrac{d}{dx}({{x}^{5}}) \right\}\]

Now we use equation (ii) to solve this differential. So, we have,

\[\dfrac{dy}{dx}=\dfrac{1}{4x-{{x}^{5}}}(4-5{{x}^{4}})\]

By further simplification we can write,

$\dfrac{dy}{dx}=\dfrac{4-5{{x}^{4}}}{4x-{{x}^{5}}}$

Hence, the answer is $\dfrac{4-5{{x}^{4}}}{4x-{{x}^{5}}}$

Note:

We should also keep in mind the base of the logarithm when we are differentiating. We must make the base of logarithm as e when we try to differentiate as equation (i) is only valid when the base is e.

There can be another way to solve this differentiation.

As we know,

${{\log }_{a}}b=c\Rightarrow b={{a}^{c}}$

We can use the following result too in our question and proceed.

We have, $y=\log (4x-{{x}^{5}})$

Using the above property we can write,

$4x-{{x}^{5}}={{e}^{y}}$

Again we can differentiate with respect to x both sides and proceed.

$\dfrac{d}{dx}(4x-{{x}^{5}})=\dfrac{d}{dx}({{e}^{y}})$

Now we can apply chain rule and proceed as earlier,

$(4-5{{x}^{4}})={{e}^{y}}\dfrac{dy}{dx}$

Dividing both sides with ${{e}^{y}}$ we have,

$\dfrac{dy}{dx}=\dfrac{4-5{{x}^{4}}}{{{e}^{y}}}$

Substituting y we have,

$\dfrac{dy}{dx}=\dfrac{4-5{{x}^{4}}}{{{e}^{\log (4x-{{x}^{5}})}}}$

Now we need the following property of exponential: ${{a}^{{{\log }_{a}}b}}=b$

Therefore, we can write

$\dfrac{dy}{dx}=\dfrac{4-5{{x}^{4}}}{4x-{{x}^{5}}}$

As we can see by both methods we get exactly the same answer.

Last updated date: 20th Sep 2023

•

Total views: 359.4k

•

Views today: 8.59k